The Comparison of Numbered Head Together Learning Models and Think Pair Share in terms of Elementary School Mathematics Learning Outcomes - Baskoro, Rainaldy Ade (International Journal of Elementary Education, 2020)
This research that will be conducted is a meta-analysis study carried out by combining two or more studies with the dependent variable, which is combined into one. The Meta-Analysis Research Design summarises, reviews, and analyses research using articles that have previously examined the Numbered Heads Together and Think Pair Share learning models. Research variables are formed into whatever is applied by the researcher as a lesson. Information can be obtained about it. Then conclusions will be drawn. This study has two variables: the independent variable (X: Numbered Head Together and Think Pair Share) and the dependent variable (Y: Judging from elementary school mathematics learning). Data collection is carried out by research by searching for relevant articles or related to the topic studied in an internet network situation. The data analysis technique used in this study is the effect size analysis technique. The effect size formula used is the effect size formula with the eta squared formula ('n2). Overall, cooperative learning can improve students' mathematics learning outcomes in the control group's experimental group. Aspects at the level of education in the analysis of the application of idik. The score of the influence of the elementary school level. These results indicate that the cooperative learning model in all areas studied improved students' mathematics learning outcomes in the experimental group.